2014
DOI: 10.1177/1403494813520354
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment among breast cancer survivors

Abstract: Duration of unemployment before breast cancer was the most important determinant of unemployment after breast cancer treatment. This allows identification of a particularly vulnerable group of patients in need of rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 23 publications
3
36
1
2
Order By: Relevance
“…We found that cancer survivors were more likely to be employed for pay during the study follow-up period. These findings differ from those of several longitudinal studies, which found that either cancer survivors were less likely to be employed than non-survivors, or that there were no significant differences in employment outcomes between the two groups [18][19][20][21][22][23]28,29]. Additionally, unlike previous studies [26,40], we found that indicators of health status such as fatigue and depression were not associated with employment outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that cancer survivors were more likely to be employed for pay during the study follow-up period. These findings differ from those of several longitudinal studies, which found that either cancer survivors were less likely to be employed than non-survivors, or that there were no significant differences in employment outcomes between the two groups [18][19][20][21][22][23]28,29]. Additionally, unlike previous studies [26,40], we found that indicators of health status such as fatigue and depression were not associated with employment outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…among women. However, results have been mixed [18][19][20][21][22][23][24][25][26][27][28][29], and only a limited number of long-term (>5 years) studies have investigated the role of occupation type in women's employment outcomes after cancer. In a Danish population-based study, cancer survivors had a higher likelihood of unemployment during the 20 years of follow-up than persons without a cancer history, and manual work was a significant predictor of unemployment [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there were significantly more survivors with the SC who worked part-time or who were on sick leave or disabled than those without the SC. Cancer-related symptoms such as pain, fatigue, and psychological distress have been associated with unemployment in several studies, but all these studies have investigated one symptom at a time [23][24][25]. To our current knowledge, the present study is the first to show that the SC of pain, fatigue, and psychological distress after breast cancer treatment is associated with reduced ability to work for many years after the diagnosis.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 57%
“…Getting patients back to work is one of the first and most important goals after treatment is completed. However, several studies have shown that breast cancer survivors have an increased risk of unemployment [21,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%